Development of a facile one-pot synthesis method for an ingestible pH sensitive actuator. (2020) - Keller, Alex; Warren, Holly; Panhuis, Marc in het
ABSTRACT: Edible devices are an emergent technology and in this paper the simplicity and efficacy that poly(acrylic acid)/calcium hydroxide possess in creating a pH sensitive ingestible actuator which responds to acidic environments such as gastric fluid is demonstrated. It was found that poly(acrylic acid)/calcium hydroxide hydrogels exhibit reversible actuation upon submerging in 0.1 M sodium citrate for 2 hours. Our results show that these hydrogels can restore their compressive stress to 0.19 ± 0.06 MPa, swelling ratio to 26 ± 2 and volume to 56% ± 3% of its original volume. This work offers new possibilities for developments in a variety of fields such as drug delivery, 4D printed materials, soft robotics and edible devices.